Peran Kateketika dalam Membentuk Iman Kekristenan - Halitopo, Robertho Nickho Sandrio (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2024)
The role of catechesis is very important in efforts to grow and shape the Christian faith of the congregation in the church and has a great responsibility for the faith of the congregation in the church. That is why catechesis must play a role in forming faith. If there is no good role for catechesis, this will affect the growth and quality of the Christian faith, then catechesis must play an active role in its role. The aim of applying catechesis in the church is to form and grow and mature the congregation's faith in the Lord Jesus Christ as Lord and Savior of mankind. The aim of applying catechism in forming the Christian faith is not only for adult congregations, but also applied to congregations who are still children. children to the elderly. With the good role of catechesis, it is hoped that the role of catechesis can shape the Christian faith in the church. There is also a qualitative research method through literacy and literature used in writing this journal article, to examine the role of catechetics in forming the Christian faith.